Berebut Kontrol Atas Sumber Daya Alam: Pertarungan Elit Dalam Memperebutkan Potensi Ekonomi Tambang Artisanal - Arif Akbar; Delfi Suganda; Marhadia Nengsy (Jurnal Community, 2025)
Abundant natural resources will become a continuous problem if not managed properly, one example is the existence of natural resources, namely gold in Gampong Gunong Rotan, Labuhan Haji Timur District. In this village there is a potential natural resource of gold which is a resource for many people, including workers, landowners and investors. This research is a type of qualitative research, with data collection methods using interviews and observations at the research location. By borrowing the theory of patron client, it was found that the involvement of investors in the shrinking of natural resources in the area of Gampong Gunong Rotan, Labuhan Haji District, is a chain of dependency between patrons and clients that has positive and negative impacts. The positive impact helps the economy of the families of workers who work in mining wells, while the negative impact is that investors compete to control areas that have gold potential at the mining